(untitled) (Marketing Journal, 2025)
The article examines the transformation of tourism activities under the influence of digital technologies. It highlights key digital tools such as mobile applications, big data, artificial intelligence, and blockchain, which shape new formats of service, marketing, and communication. The study analyzes international and national case studies of digital innovation in tourism. It emphasizes the need for adaptation of tourism businesses to the digital environment.